Analisis Kinerja Keuangan pada Perusahaan CV Yanidilla Adilindo (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the financial performance of CV Yanidilla Adilindo by using financial ratios, including liquidity, solvency, profitability, and activity ratios. The data used in this research consists of the company's financial statements for the last two years, including the income statement, balance sheet, and cash flow statement. Through the analysis of financial ratios, this study seeks to assess the effectiveness and efficiency of the company’s financial resource management and provide an overview of its strengths and weaknesses in financial aspects. The findings indicate that the company experienced fluctuations in financial performance, with some ratios showing improvement, while others exhibited a decline that requires further attention. Based on these findings, it is recommended that the company improve liquidity management and optimize its financing structure to support future financial stability.